Correlation between thyroid dysfunction and efficacy of immune checkpoint inhibitors in patients with advanced solid tumors - Cheng Zhao (Discover Oncology)
Abstract Background Immune checkpoint inhibitors (ICIs) are currently the first line of tumor immunotherapy for the treatment of a wide range of tumors. However, the main side effect of immune checkpoint inhibitors is that they cause immune-related adverse events (irAEs) in patients. The relationship between the occurrence of immune side effects in patients and efficacy is controversial. The objective of this study was to confirm the relationship between patients who develop thyroid dysfunction after immune checkpoint inhibitors and efficacy. Methods This study was a retrospective real-world clinical study, and a total of 50 patients with advanced tumors treated with immune checkpoint inhibitors at Anqing People's Hospital from 2020.8 to 2022.5 were retrospectively collected. Among them, 30 patients with hypothyroidism and 20 patients with normal or hyperthyroidism occurred, and the treatment effects and prognostic differences between the two groups were compared. Finding After PD1 treatment in all patients, there were 10 cases of partial remission(PR), 18 cases of stable disease(SD) and 2 cases of progressive disease(PD) in patients who developed hypothyroidism, with a disease control rate(DCR) of 93.3% and objective remission rate(ORR) of 33.3%. There were 0 complete remission (CR) patient, 3 PR patients, 11 SD patients, 6 PD patients, 70.0% DCR and 15.0% ORR in patients who did not develop hypothyroidism. The DCR and ORR of patients who developed hypothyroidism were better than those of non-hypothyroid patients, and the difference was statistically significant (P < 0.05). Kaplan–Meier survival analysis showed that progression-free survival (PFS) reached 9.2 months (95% CI 7.726–10.779) in patients who developed hypothyroidism and did not hypothyroidism patients have a PFS of 7.3 months (95% CI 5.604–8.505), with a statistically significant difference (P = 0.0341 < 0.05). Further subgroup analysis revealed that among patients who developed hypothyroidism, PFS was 3.3 months (95% CI 0.630–5.440) in patients with cholangiocarcinoma, 6.89 months (95% CI 5.604–8.505) in patients with non-small cell lung cancer, > 12 months in patients with hepatocellular carcinoma, and 11.05 months (95% CI 9.308–12.792) in patients with esophageal cancer months and PFS for patients with gastric cancer was 9.74 months (95% CI 6.979–12.502). Interpretation When patients with advanced tumors were treated with immune checkpoint inhibitors, DCR and ORR were higher in patients who developed hypothyroidism, and patients had better PFS. The benefits were greater in patients with gastric, esophageal, and hepatocellular carcinomas.